Seed shape and size of Silene latifolia, differences between sexes, and influence of the parental genome in hybrids with Silene dioica - Hubinský, Marcel; Martín-Gómez, José Javier; Cervantes, Emilio; Hobza, Roman; Rodríguez Lorenzo, Jose Luis (Frontiers in Plant Science, 2024)
Introduction Plants may undergo different natural changes, which dramatically modify their genomes. One is polyploidization, the second is hybridization. Both are regarded as key factors for plant evolution and result in differences in phenotype in the different plant organs. In Silene, we can find both examples in nature, and this genus has a seed shape diversity long recognized as a valuable source of information for infrageneric classification. Methods Morphometric analysis is the statistical study of shape and size and their covariations with other variables. Traditionally, seed shape description was limited to an approximative comparison with geometric figures (rounded, globular, reniform or heart shaped). Seed shape quantification has been based on direct measurements such as area, perimeter, length or width, narrowing statistical analysis. We used seed images and processed them to get their silhouettes. We performed geometric morphometrics analysis, such as similarity to geometric models and elliptic Fourier analysis to study the hybrid offspring between S. latifolia and S. dioica. Results We generated synthetic tetraploids of Silene latifolia and performed controlled crosses between diploid S. latifolia and Silene dioica as an approach to analyse seed morphology. After imaging capture and postprocessing, statistical analysis revealed differences in seed size, but not in shape between S. latifolia diploids and tetraploids and also some differences in shape among the parentals and the hybrids. A detailed inspection through fluorescence microscopy allowed the identification of shape differences in the cells of the seed coat. In the case of the hybrids, differences were found in circularity and solidity. Overal seed shape is maternally regulated for both species, while cell shape cannot be associated to any of the sexes. Discussion Our results provide additional tools useful in combination of morphology with genetics, ecology or taxonomy. Seed shape is a robust indicator that can be used as a complementary tool for genetic and phylogenetic analysis in Silene hybrid populations.